2014
DOI: 10.2478/ijpeat-2013-0009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Runway Deflectometer Campaign for Implementation on Airport Pavement Management System

Abstract: The load-carrying capacity, is one of the indicators used to assess airfield pavement conditions. It could be estimated by evaluating the response of stationary dynamic loads, using a deflectometric device that simulates the stress inducted by an aircraft moving at moderate speed. This device is widely used because tests are nondestructive and rapid to execute and can be conducted for cyclic investigations, providing valuable support to maintenance and rehabilitation (M&R) decision makers through pavement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The improvement of new optimized tools, which could be easily applied to assess the pavement conditions subjected to aircraft loads without extreme costs, has become a critical objective of airport owners. The gathered data by in situ tests and often collected without comparable conditions, such as the temperature of the asphalt surface and moisture content of subgrades, can be used to estimate structural conditions of airport pavements for the conduction on budgeting, planning, programming, and prioritization of Airport Pavement Management System (APMS) and the selection about the appropriate actions of Maintenance and Rehabilitation (M&R) [14,19]. The load-carrying capacity is the most important indicator adopted to assess airport pavement conditions using the in situ tests to estimate the structural response of stationary dynamic loads [6].…”
Section: Back Calculation Methods Used For Fwd and Hwd Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement of new optimized tools, which could be easily applied to assess the pavement conditions subjected to aircraft loads without extreme costs, has become a critical objective of airport owners. The gathered data by in situ tests and often collected without comparable conditions, such as the temperature of the asphalt surface and moisture content of subgrades, can be used to estimate structural conditions of airport pavements for the conduction on budgeting, planning, programming, and prioritization of Airport Pavement Management System (APMS) and the selection about the appropriate actions of Maintenance and Rehabilitation (M&R) [14,19]. The load-carrying capacity is the most important indicator adopted to assess airport pavement conditions using the in situ tests to estimate the structural response of stationary dynamic loads [6].…”
Section: Back Calculation Methods Used For Fwd and Hwd Testsmentioning
confidence: 99%
“…The load-carrying capacity is the most important indicator adopted to assess airport pavement conditions using the in situ tests to estimate the structural response of stationary dynamic loads [6]. To evaluate the structural capacity of pavement, the deflectometer devices, such as the Falling Weight Deflectometer (FWD) and the Heavy Weight Deflectometer (HWD), have been widely employed to simulate the impact on pavement structures induced by an aircraft moving at moderate speed because these tests are nondestructive and rapid to execute for cyclic investigations [19]. The FWD test has been widely used to test the material properties of road and airport pavements [3].…”
Section: Back Calculation Methods Used For Fwd and Hwd Testsmentioning
confidence: 99%
“…Framework para análise visual de módulos de elasticidade Pigozzi et al (2014) propõem um framework para avaliar a capacidade estrutural de pavimentos aeroportuários usando dados de deflexão coletados por HWD. Os dados são coletados e analisados de forma padronizada e, então, é realizada a representação por mapas de calor da distribuição dos valores ao longo da pista.…”
Section: Software De Retroanálise Backcapunclassified
“…Um mapeamento simples de acordo com a região da medição é realizado e então colorido para que haja uma representação visual que auxilie a tomada de decisão quanto às áreas de interesse. Pigozzi et al (2014), no entanto, ampliaram a proposta a um framework que mapeia detalhadamente no pavimento as regiões classificadas pelos dados.…”
Section: Software De Retroanálise Backcapunclassified
“…Falling-weight deflectometer (FWD) works on the principle of application of transient impulse-type load on the surface of the pavement to measure the deflection response of its layers (IRC -Indian Road Congress, 2014. HWD, which is similar in principle to FWD, is suitable for airfield pavements, as its evaluation necessitates the application of heavier loads to simulate aircraft loading (Pigozzi et al, 2014;Turner et al, 2003). Researchers in the previous studies have reported useful findings from the varied applications of these devices.…”
Section: Literature Reviewmentioning
confidence: 99%